Aplikasi Sistem Pakar Diagnosis Penyakit Menular Pada Balita Dengan Metode Forward Chaining - Tjumoko, Yohan Kurnia Putra; Sukmaaji, Anjik; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2012)
Infectious diseases are diseases that are harmful to infants because it can spread rapidly. Delay in treatment of diseases can cause more severe disease and difficult to cure. Cost to consult the experts are not cheap. Therefore parents need a system that has the ability as an expert for diagnosis of disease. Expert system diagnosis of infectious diseases in infants was built for the diagnosis of tropical diseases attributable to virus infection, fungus and bacteria. With this system parents can get answers to infectious diseases suffered by their toddlers. The system provides information on diagnosis, treatment and prevention. The system uses a forward chaining method. This method of tracking each patient's symptoms, mencokkannya with existing rules, and produces a diagnosis based on the knowledge base. The test result with expert knowledge system diagnosis indicates that the system is capable of detecting the disease and provide treatment based on symptoms that have been experienced by users. Keywords: expert systems, forward chaining, infectious diseases infants